Sensory overload: A concept analysis. (9th February 2017) - Scheydt, Stefan; Müller Staub, Maria; Frauenfelder, Fritz; Nielsen, Gunnar H.; Behrens, Johann; Needham, Ian
Abstract: In the context of mental disorders sensory overload is a widely described phenomenon used in conjunction with psychiatric interventions such as removal from stimuli. However, the theoretical foundation of sensory overload as addressed in the literature can be described as insufficient and fragmentary. To date, the concept of sensory overload has not yet been sufficiently specified or analyzed. The aim of the study was to analyze the concept of sensory overload in mental health care. A literature search was undertaken using specific electronic databases, specific journals and websites, hand searches, specific library catalogues, and electronic publishing databases. Walker and Avant's method of concept analysis was used to analyze the sources included in the analysis. All aspects of the method of Walker and Avant were covered in this concept analysis. The conceptual understanding has become more focused, the defining attributes, influencing factors and consequences are described and empirical referents identified. The concept analysis is a first step in the development of a middle‐range descriptive theory of sensory overload based on social scientific and stress‐theoretical approaches. This specification may serve as a fundament for further research, for the development of a nursing diagnosis or for guidelines.